The role of teachers in increasing the scientific literacy of early childhood - Sakina; Hapidin, Hapidin; Nurani, Yuliani (Exploration in Early Childhood Research, 2024)
Early childhood education provides services in developing and facilitating children's growth and development in a safe and enjoyable atmosphere. Teachers are required to develop these services in the form of fun learning activities according to the child's age and level of development. Scientific literacy is one of the abilities that must be developed in early childhood. However, based on the results of field surveys through interviews with early childhood teachers from several kindergartens in Depok City, it shows that teachers' abilities in designing science based learning activities are still limited to simple science experiment activities. Teachers have not optimally used the surrounding environment as a learning resource and medium. Based on the problems found, this research aims to analyze teachers' abilities in designing fun science play activities. Researchers used literature studies to determine the role of teachers in introducing science content through fun play. A qualitative descriptive analysis method was used to describe the results of this research. The research results obtained show that the teacher's ability to introduce science content through fun activities will make it easier for children to understand science content. The better teachers understand science content and develop it in the form of fun play activities, the easier it will be for children to have an understanding of science and meaningful experiences.